Improving Students’ Speaking Skills through Watching Western Movie at MA Islamiyah Ciputat - Imroatul Khoiriyah; Franscy; Heri Wardana (Samudra Publisher, 2024)
This is a Classroom Action (PTK) type of research, and the subjects are students in class XI IIS Islamiyah Ciputat. The purpose of this study is to determine the results of improving students' ability to speak through movie media. Classroom Action Research uses the Kemmis & Mc. Teggart model, which consists of four stages: planning, implementation, observation, and reflection. Data were collected through observation, tests, interviews, and documentation. The study was conducted in two cycles, with two meetings per cycle. The results show that film media can improve the speaking ability of students in class II C at SDN Ciputat 01. In cycle I, the class average score was 68.08, and 56% of the students completed. Based on this explanation, it can be said that students of class XI IIS Islamiyah Ciputat can improve their speaking skills by using movie media.